(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
An Ethenomedicinal survey was done in the month of august to september 2019, in differentarea of Chaturgarh forest and ethenomedicinal knowledge were collected through inhibited tribes andlocal peoples called vaidya or baiga. This forest area is inhibited in korba district. Climatic condition ofthis region in general wet and humid type. This region have large tribal population of Gond, Baiga,Bhumiya ,Binjhwar ,Halwa, Kanwar, Korwa, Hilly Korwa, Khariya, Agariya, Halba, Hulbi, etc. Many smallvillages are present in this forest region. During the survey knowledgeable person, vaidya, wereinterviewed and information recorded. The data indicate the uses of 30 ethnomedicinal plants used tocure different disease. Ethenomedicinal plants are Curcuma aromatica, hemedesmus indicus,elephantopusscaber, celastruspaniculatus, andrographispaniculata, swertiachirata, abutilon indicum,achyranthus aspera, boerhaviadiffusa, dioscoreabulbifera etc. We find that important knowledge ofmedicinal plants gathered by the Trible are needs to be determined in order to develop plans for theirprotection, improving awareness, proper documentation of indigenous knowledge about the plantsused by them.